Some data on ecological characteristics of harmful microalgae cultured in the laboratory - Thuoc, Chu Van; Minh Huyen, Nguyen Thi (Academia Journal of Biology, 2015)
The cultivation results of some harmful marine microalgal species showed that, in the same cultured conditions of nutrient, salinity, temperature, Alexandrium tamarense grew in the high light intensity better than in the lower ones. It grew better in the salinity of 16 ppt than that of 10 and 21ppt. The changes of salinity have not effected strongly to the growth of Coolia monotis and Amphidinium carterae. In generally, A. carterae grew well not only in the lower temperature (15oC) but also in the higher one (30oC) while some species such as: Prorocentrum lima, P. emarginatum, P. mexicanum and Coolia monotis are effected by the changes of temperature.